COVID-19 Vaccine Hesitancy: Disadvantaged Groups’ Experience with Perceived Barriers, Cues to Action, and Attitudes - Coman, Ioana A; Xu, Shan; Yamamoto, Masahiro (American journal of health promotion, 2023)
Purpose Drawing from the Health Belief Model, we explored how disadvantaged groups in the U.S., including Black, Hispanic, less educated and wealthy individuals, experienced perceived barriers and cues to action in the context of the COVID-19 vaccination. Design A cross-sectional survey administered in March 2021. Setting USA Subjects A national sample of U.S. residents (n = 795) recruited from Prolific. Measures Perceived barriers (clinical, access, trust, religion/spiritual), cues to action (authorities, social circles), attitudes toward COVID-19 vaccination. Analysis Factor analysis and Structural Equation Model (SEM) were performed in STATA 16. Results Black and less educated individuals experienced higher clinical barriers (CI [.012, .33]; CI [.027, .10]), trust barriers (CI [.49, .92]; CI [.057, .16]), and religious/spiritual barriers (CI [.28, .66]; CI [.026, .11]). Hispanics experienced lower levels of clinical barriers (CI [-.42, .0001]). Clinical, trust, and religious/spiritual barriers were negatively related to attitudes toward vaccination (CI [-.45, −.15]; CI [-.79, −.51]; CI [-.43, −.13]). Black and less educated individuals experienced fewer cues to action by authority (CI [-.47, −.083]; CI [-.093, −.002]) and social ties (CI [-.75, −.33]; CI [-.18, −.080]). Lower-income individuals experienced fewer cues to action by social ties (CI [-.097, −.032]). Cues from social ties were positively associated with vaccination attitudes (CI [.065, .26]). Conclusion Communication should be personalized to address perceived barriers disadvantaged groups differentially experience and use sources who exert influences on these groups.